2007
DOI: 10.1093/geront/47.4.535
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Remaining in the Community After Discharge: Results From New Jersey's Nursing Home Transition Program

Abstract: Purpose: To inform states with nursing home transition programs, we determine what risk factors are associated with participants' long-term readmission to nursing homes within 1 year after discharge. Design and Methods: We obtained administrative data for all 1,354 nursing home residents who were discharged, and we interviewed 628 transitioning through New Jersey's nursing home transition program in 2000. We used the Andersen behavioral model to select predictors of long-term nursing home readmission, and we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…In this model, predisposing factors, such as age, may externally influence readmission, while enabling factors, such as insurance or Community Ment Health J financial status make it possible for readmission to occur. Further, factors of need, such as having severe symptoms, may be necessary for readmission (Chan et al 2008;Howell et al 2007). While the variables in the present study were selected based on previous psychiatric readmission literature, Andersen's model may be useful in understanding why factors such as payer and employment status can be influential to patient readmission, while others, such as age, may be associated with readmission in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, predisposing factors, such as age, may externally influence readmission, while enabling factors, such as insurance or Community Ment Health J financial status make it possible for readmission to occur. Further, factors of need, such as having severe symptoms, may be necessary for readmission (Chan et al 2008;Howell et al 2007). While the variables in the present study were selected based on previous psychiatric readmission literature, Andersen's model may be useful in understanding why factors such as payer and employment status can be influential to patient readmission, while others, such as age, may be associated with readmission in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of risk factors for readmission into NHs within one year of discharge, a study of New Jersey's nursing home transition program identified that 72.6% of participants remained in the community (Howell, Silberberg, Quinn, & Lucas, 2007). This study identified that (1) being male, single, and dissatisfied with one's living situation; (2) living with others; and (3) falling within 8 to 10 weeks after discharge were significant predictors of NH readmission.…”
Section: Supporting Transitions Between Nursing Home and Community Sementioning
confidence: 95%
“…Recent development of nursing home transition programs demonstrates that nursing home residents can return to community settings. Through the linkage to HCBS, the nursing home transition program in New Jersey provides information about the full range of long-term care options, and has helped about three quarters of the participants remain in the community during the first year after leaving a nursing home (Howell et al, 2007).…”
Section: Effects Of Hcbs Utilizationmentioning
confidence: 99%
“…One such solution is to expand homeand community-based services (HCBS; Golant, 2009). Increasing numbers of older adults-especially the oldest-old (those aged 85 and older) and those aging with disabilities-have created an increasing demand for a broad array of HCBS (Borrayo, Salmon, Polivka, & Dunlop, 2002;Howell, Silberberg, Quinn, & Lucas, 2007). The traditional long-term care that entailed longterm placement in a nursing home institution has given way to transient post-acute and rehabilitation placement, assisted living facilities, and HCBS programs (adult day care, meals-on-wheels, home health care, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation